FindItHere: Lost and Found Item Matching Web Application - Murugiah, Vimalnath; Mat Nawi, Rosmamalmi (Applied Information Technology And Computer Science, 2025)
The ‘FindItHere’ project addresses the problem of effectively managing lost and found items in Universiti Tun Hussein Onn campus. It may be stressful to lose personal belongings, and it gets worse by the absence of an organised platform to connect people who lose or found items. Users can provide information about found belongings or report lost items on this system’s organised, user-friendly website. The goal is to improve user and administrator collaboration to simplify and quicken the lost item recovery process. The project uses the Agile methodology, which enables continuous development and feedback to improve functionality and features. The methodology involves dividing the project into smaller phases, each of which concentrates on developing key elements like user registration, reporting, and notification features. Real-time notifications for matched items, an admin dashboard for tracking user activity, and a user-friendly interface for submitting reports are some of the main features. ‘FindItHere’ provides a complete lost-and-found management system that facilitates better interaction between administrators and users. By offering an easy and effective method for tracking and recovering lost items, the system improves user satisfaction.